Continuity of care and its effect on readmissions for COPD patients: A comparative study of Norway and Germany. Issue 7 (July 2018) - Swanson, Jayson O.; Vogt, Verena; Sundmacher, Leonie; Hagen, Terje P.; Moger, Tron Anders
Highlights: Despite Norwegian patient lists and gatekeeping, results suggest higher continuity in Germany. Association between continuity before hospitalization and readmissions was only observed in Norway. Continuity measured after discharge was associated with readmissions in both countries. Abstract: Background: This study compares continuity of care between Germany – a social health insurance country, and Norway – a national health service country with gatekeeping and patient lists for COPD patients before and after initial hospitalization. We also investigate how subsequent readmissions are affected. Methods: Continuity of Care Index (COCI), Usual Provider Index (UPC) and Sequential Continuity Index (SECON) were calculated using insurance claims and national register data (2009–14). These indices were used in negative binomial and logistic regressions to estimate incident rate ratios (IRR) and odds ratios (OR) for comparing readmissions. Results: All continuity indices were significantly lower in Norway. One year readmissions were significantly higher in Germany, whereas 30-day rates were not. All indices measured one year after discharge were negatively associated with one-year readmissions for both countries. Significant associations between indices measured before hospitalization and readmissions were only observed in Norway – all indices for one-year readmissions and SECON for 30-day readmissions. Conclusion: Our findings indicate higher continuity is associated with reductions in readmissions following initial COPD admission. This is observed both before and after hospitalization in a system with gatekeeping and patient lists, yet only after for a system lacking such arrangements. These results emphasize the need for policy strategies to further investigate and promote care continuity in order to reduce hospital readmission burden for COPD patients.